Main controlling factors of marine shale compressive strength: A case study on the cambrian Niutitang Formation in Dabashan Mountain. (1st December 2022) - He, Qianyang; Li, Delu; Sun, Qiang; Wei, Baowei; Wang, Shaofei
Abstract: Lower Paleozoic shale is an important hydrocarbon source rock and natural gas reservoir in the Upper Yangtze Plate. In this study, compressive strength + acoustic emission (AE), low-pressure nitrogen adsorption and desorption (LP-N2 A), low-field nuclear magnetic resonance (NMR), total organic carbon (TOC), X-ray fluorescence spectroscopy (XRF), scanning electron microscopy (SEM) and other experiments were carried out on the marine shale of the Cambrian Niutitang Formation in Fucheng Town, Dabashan Mountain. The results showed that: 1) The compressive strength of shale with an average of 58.38 MPa, and its rupture process can be divided into four stages; 2) The high proportion of mesopores in shale is significantly negatively correlated with compressive strength; 3) TOC in shale averaging 2.37 wt% was positively correlated with compressive strength; 4) The main element was SiO2 averaging 68.47 wt%, which is positively correlated with compressive strength. Meanwhile, Al2 O3, Fe2 O3 and CaO + MgO content were negatively correlated with compressive strength. To sum up, the organic and quartz content in shale jointly increase the compressive strength of shale, while the mesopores proportion has a constraining effect on the compressive strength. This study provides geological information and a theoretical basis for shale fracture development. Highlights: Combination of petrophysical and geochemical parameters of marine shale. The concentration of organic and silica increase the compressive strength. The mesopore proportion has a constraining effect on the compressive strength.